Kritik Sosial Dalam Kumpulan Puisi W.S Rendra: Kehidupan Masyarakat di Indonesia - Debby Alya Pratiwi; Indah Safitri; Lilatul Farika (CAKRAWALA LINGUISTA, 2018)
The poetry of research by W.S Rendra is aimed to describe social condition of society in Indonesia. Social conditions are in the form of social status, poverty, and arbitrariness of the government. The theory used to examine these poems is the theory of genetic structuralism and uses the sociological approach of the work. The method used in this research is qualitative research. The data source used is 3 poems by W.S Rendra. While the data is a quote from a collection of poems W.S Rendra which contains elements of social criticism. Data collection techniques used in this study is literature study techniques. In this research data collection is by reading the collection of poems by W.S Rendra and look for aspects that contain elements of social criticism in a collection of poems by W.S Rendra. The data research procedure used is reading poetry, collecting data in the form of quotation. Data analysis technique used is content analysis technique. The results of this study indicate that there are several social problems in Indonesia that have been criticized by W.S Rendra into a poem of his creation.